Pregnancy rates of holstein cows after postinsemination treatment with progesterone - Stevenson, Jeffrey S.; Mee, M. O. (Kansas Agricultural Experiment Station, 2011)
The objective of this experiment was to determine if pregnancy rates following first services would be improved by supplementing lactating dairy cows with progesterone during two phases after insemination. Cows were inseminated at estrus (day 0), and progesterone was administered via a progesterone-releasing intravaginal device (PRID) from days 5 to 13 or days 13 to 21 after first service with untreated cows serving as controls. Pregnancy rates at first services were unaffected by the progesterone treatments whether the cows received a PRID from days 5 to 13 (13/36 or 36%), a PRID from days 13 to 21 (18/36 or 50%), or no PRID (39/92 or 42%). Fewer nonpregnant cows receiving the PRID returned to estrus 17 to 27 days after the first service compared to the controls (27 vs. 49%). However, this apparently was not associated with improved embryonic survival in the cows receiving progesterone because the pattern of cows returning to estrus after first service was similar, except for 17 to 27-day period cited above. Supplementing progesterone to lactating dairy cows after first services did not seem to improve fertility.
Keywords: Dairy; Pregnancy rates; Cows; Progesterone